DEIKSIS DALAM FILM GOD’S NOT DEAD KARYA HAROLD CRONK - Tumoka, Edwin Edwar; Pelealu, Hetty; Manus, Jeane Angela (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACT               This research entitled "Deiksis dalam film God’s Not Dead Karya Harold Cronk"The purpose of this study is to identify and classify the types of deixis and analyze the use of deixis in the film God’s Not Dead by Harold Cronk. The method used in this research is descriptive method. The data used in this study were taken from sentences in the film God’s Not Dead. Data analysis uses Levinson's theory.The results of this study indicate that there are 5 types of deixis in film God’s Not Dead, those are person  deixis (first person: I, I'm, mine, me, we, second person: You, your, yourself and third person: They, them, he, she's, his, everyone). Place deixis: World, Podium, Classroom, Pool, Roman Colosseum, La Rive Gauche, Park, Class, In front of a room, Dakar, Zurich, Zurich, Frankfurt, Frankfurt and Carter International. Time deixis: Next Friday, 3 sessions, 20 minutes, Some 13.7 billions years ago, 2500 years, Next week’s, Tomorrow, 2000 years ago, Year, One day and All the time. Discourse deixis : That, This, Those, It's. Social deixis: Prosecutor, Defense attorney, Jury, My friend, Ladies, Gentleman, Brave young freshman, My father, Honey, Meciful Father, Silly boy, Minority, Freshman. While the analysis related to the use of deixis in the film Gods Not Dead found the use of gestural deixis and symbolic deixis. It is hoped that this research can add readers' insights on Pragmatics especially deixis. Keyword : Pragmatic Analysis, Deixis, Film, Gods Not Dead